(untitled) (Journal of International Studies, 2020)
During the cold war period, the problem of Laos was exacerbated due to strategic location of Laos and national interest of external actors. The present paper would analyze various ramifications of the conflict in Laos. Beginning from First Indochina War (1946-1954), fate of Laos was linked very closely with that of Vietnam. With the escalation of conflict, a solution to problem of Laos was nowhere in sight. The Geneva Conference of 1954 did not solve the problem. The three major strands in Laos; Pathet Lao, neutralists and the rightists became a constant feature of Lao politics. Both the United States and North Vietnam came into conflict, as they were committed to help their respective allies in Laos, and regarded the other’s action in Laos as harmful to their interest in South Vietnam. An agreement on Laos became contingent upon ending the war in Vietnam. The net result of outside intervention was prolongation of conflict in Laos. A solution to Lao conflict was in sight after the Geneva accords of 1962. However, the gradual linkage of the country with the Vietnam War made the solution of dependent upon the outcome of conflict in Vietnam. Laos was going to be embroiled in the Vietnam War and there was no peace in sight unless a solution was there in Vietnam. Laos became a sideshow in Vietnam War.